Peningkatan Keterampilan Menulis Karangan Narasi Menggunakan Picture Word Inductive Model (PWIM) di Kelas IV D SDS IT Dar El Iman - Monica Puspa Cahyani; Chandra; Adrias; Nana Fauzana Azima (STKIP Subang, 2025)
This classroom action research was conducted to improve narrative writing skills among fourth-grade students in Class IV D at SDS IT Dar El Iman. Initial observations indicated that students faced difficulties in generating ideas, had limited vocabulary, and struggled to produce engaging narrative texts. To address these issues, the Picture Word Inductive Model (PWIM) was implemented as an instructional strategy. The study employed both qualitative and quantitative approaches and was carried out over two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. Data were collected through tests and non-test instruments, with participants including the classroom teacher as an observer, the researcher as the instructor, and 26 fourth-grade students. The findings revealed a consistent improvement in students’ narrative writing skills from the first to the second cycle. The evaluation of the teaching module increased from 87.50% (Good) to 100% (Very Good). Teacher activity observations rose from 87.25% to 97.91%, while student engagement improved from 77.08% to 95.83%. These results demonstrate that the application of PWIM effectively enhances students' ability to write narrative texts.